2009
DOI: 10.1007/s11806-009-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial dynamics of cropland and cropping pattern change analysis using landsat TM and IRS P6 LISS III satellite images with GIS

Abstract: The study of the spatial patterns and temporal changes of cropland is important to understand the underlying factors and the functional effects of the agricultural landscape. On the other hand, crop dynamics mapping is essential to know the overall agro-spatial diversity of the area. Therefore, this paper addressed a spatio-temporal analysis of cropland and cropping pattern change in the Bogra district of Bangladesh over the last 16 years (between 1988/89 and 2004/05). In this paper, crop mapping from multi-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Understanding the dynamics of forest loss is critical for the planning and protection of biodiversity [21] [22]. Insights into patterns, rates, and trends of landscape changes are necessary to realize forest dynamics, enable preservation, and evaluate the effectiveness of management approaches [22] [23]. Land cover changes may result from human-induced land use changes or natural processes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the dynamics of forest loss is critical for the planning and protection of biodiversity [21] [22]. Insights into patterns, rates, and trends of landscape changes are necessary to realize forest dynamics, enable preservation, and evaluate the effectiveness of management approaches [22] [23]. Land cover changes may result from human-induced land use changes or natural processes, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Spatial technologies, including geographic information system (GIS) and numerical modeling techniques, have emerged as highly effective tools for conducting ecological and environmental assessments. These technologies enable comprehensive analysis and evaluation of spatial data, facilitating a deeper understanding of ecological processes and environmental dynamics (Krivtsov, 2004;Rahman & Saha, 2007;Rahman & Saha, 2008;Rahman & Saha, 2009;Rahman et al, 2014;Rahman et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In recent, Shahidullah et al, (2017), were observed the changes in multiple crop practices over 42 Upazilas of Chittagong region in 2016 using pre-tested semistructured questionnaire with a specific view to document the existing cropping patterns, cropping intensity and crop diversity. Moreover, Rahman and Saha (2009) conducted study in Bogra district (western part of Bangladesh) to map seasonal crop land considering Landsat TM, and IRS P6 LISS-3 satellite images from 1988/89 to 2004/05 time periods using objectbased classification. However, in recent, LULC changes was observed in transformation of significant parts of the Hathazari Upazila and its quantitative assessment from 1977-2017 using Landsat MSS, TM and OLI satellite imageries (Bhuiyan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%